2021
DOI: 10.3390/plants10112506
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhiza-Induced Alterations in Metabolome of Medicago lupulina Leaves during Symbiosis Development

Abstract: The present study is aimed at disclosing metabolic profile alterations in the leaves of the Medicago lupulina MlS-1 line that result from high-efficiency arbuscular mycorrhiza (AM) symbiosis formed with Rhizophagus irregularis under condition of a low phosphorus level in the substrate. A highly effective AM symbiosis was established in the period from the stooling to the shoot branching initiation stage (the efficiency in stem height exceeded 200%). Mycorrhization led to a more intensive accumulation of phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 88 publications
2
12
0
Order By: Relevance
“…The object of the study was a model system highly responsive to mycorrhization, including Medicago lupulina MLS-1 line and Rhizophagus irregularis highly effective strain RCAM00320. Plants were grown using a phytotron by standard microvegetative method [21,22]. Plants were grown in pairs in a vessel filled with 210 g soil-sand mixture with a low level of phosphorus (the content was calculated using the Kirsanov's reaction), which was 23 mg P205 per 1 kg of soil, pHKCl -6.4.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The object of the study was a model system highly responsive to mycorrhization, including Medicago lupulina MLS-1 line and Rhizophagus irregularis highly effective strain RCAM00320. Plants were grown using a phytotron by standard microvegetative method [21,22]. Plants were grown in pairs in a vessel filled with 210 g soil-sand mixture with a low level of phosphorus (the content was calculated using the Kirsanov's reaction), which was 23 mg P205 per 1 kg of soil, pHKCl -6.4.…”
Section: Methodsmentioning
confidence: 99%
“…It should be assumed that the study of the effect of AM on the level of expression of genes-markers for the development of effective AM is the most relevant direction in both fundamental and applied research on symbiotic interactions. To solve this problem, our team previously developed a new model system "Rhizophagus irregularis + Medicago lupulina", which includes a highly effective strain of AM fungus and M. lupulina line that is characterized by high response to mycorrhization [21]. The aim of this study was to analyze the effect of inoculation with Rhizophagus irregularis effective laboratory strain RCAM00320 on the level of expression of the genes of the phosphate transporters (MlPT1, MlPT2, MlPT4) and H+-dependent ATPase, MlATP1 (where "Ml" is the abbreviation of the M. lupulina species) in the roots of a new model plant, a highly efficient M. lupulina MlS-1 line, which is characterized by high response to mycorrhization under conditions of low phosphorus levels in the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, plants are able to use proteins as specialized reserves of nitrogen and carbon accumulated into protein storage vacuoles [ 165 , 166 ]. Free amino acids are widely represented in the profiles of cell culture metabolites, and some of them are in relatively high concentration [ 157 , 158 , 167 ]. These metabolites are an important component of phloem sap, and in some cases their total concentration can be comparable to that of sucrose [ 114 , 123 , 168 , 169 ].…”
Section: Organic Substratesmentioning
confidence: 99%
“…AM fungi strongly depend on the photosynthesis products of the host plant; therefore, they have a great impact on this process [56]. We have previously shown that R. irregularis significantly increases both the content of chlorophyll a and b, and leads to a considerable increase in leaf area during the second leaf development stage, 24 DAS [49]. The importance of carbohydrate metabolism is confirmed by the results, which showed high photosynthesis activity in the presence of AM according to the assessment of the effective photochemical quantum yield of photosystem II-Y(II) at an early stage of development, with a sequential decrease at the flowering stage [49].…”
Section: Functional Categories Of Up-and Downregulated Genes By Am In...mentioning
confidence: 99%
“…The transcriptomic analysis of the model PMS "Medicago lupulina + Rhizophagus irregularis", with MGR > 350% under conditions of phosphorus (P) deficiency for plant nutrition is promising [46]. The micro-vegetative experiments in M. lupulina provided in our earlier experiments during the development of AM symbiosis showed significant changes in the course of development and hormonal rearrangements in the host plant [47,48]; metabolic rearrangements [30,49]; and changes in the expression of a number of genes for carbohydrate metabolism and P transport [50].…”
Section: Introductionmentioning
confidence: 99%